Yoga-based intervention in patients with somatoform disorders: an open label trial. (3rd May 2016) - Sutar, Roshan; Desai, Geetha; Varambally, Shivarama; Gangadhar, B. N.
Abstract: Somatoform disorders are common mental disorders associated with impaired functioning and increased utilization of health resources. Yoga-based interventions have been used successfully for anxiety, depression, and chronic pain conditions. However, literature on the use of yoga in treatment of somatoform disorders is minimal. The current study assessed the effect of a specific yoga-based intervention in patients with somatoform disorders. Consenting patients meeting ICD-10 criteria for somatoform disorders were offered a specific yoga module (1 h per day) as a treatment. Assessments including Visual Analogue Scale (VAS), Brief Pain Inventory (BPI), and others were carried out at baseline and after 2, 6, and 12 weeks. Sixty-four subjects were included in the study and 34 completed 12 weeks follow-up. Significant improvement was noted in pain severity from baseline to 12 weeks after regular yoga sessions. The mean VAS score dropped from 7.24 to 2.88. Worst and average pain score in the last 24 h on BPI dropped from 7.71 to 3.26 and from 6.12 to 2.0, 7 respectively. Results of the study suggest that yoga-based intervention can be one of the non-pharmacological treatment options in somatoform disorders. These preliminary findings need replication in larger controlled studies.